Pola Asuh Qur'ani: Studi Edukatif Surat Luqman dalam Membangun Generasi Rabbani - Aini, Syaripah; Amiruddin (Kartika: Jurnal Studi Keislaman, 2025)
This article aims to examine the Qur’anic parenting model found in Surah Luqman verses 12–19 as an educational framework for shaping a Rabbani generation. This study employs a qualitative approach using the library research method, analyzing both classical and contemporary exegeses as well as Islamic educational literature. The findings reveal that Luqman’s parenting approach encompasses five main aspects: the inculcation of tawhid (monotheism), awareness of Allah’s constant supervision, education in worship and ethics, the formation of social etiquette, and a communication style rooted in wisdom and compassion. These values play a significant role in shaping individuals who are faithful, morally upright, and socially responsible. This parenting model is not only relevant within the context of Muslim families but can also be integrated into both formal and non-formal education systems to foster an Islamic character and prepare individuals to face contemporary challenges. By using the Qur’an as the foundation of education, a holistic Rabbani generation is expected to emerge spiritually, morally, and socially grounded.